Psycholosocial assistance to students with posttraumatic stresss disorder in primary and secondary schools in post-war Bosnia Herzegovina - Hasanović, Mevludin (Array, 2009)
The 1992-1995 war in Bosnia and Herzegovina (BH) has had a tremendous impact on civilians; thousands of inhabitants were left with numerous traumatic experiences. Many children suffered or witnessed horrifying acts of violence and aggression. Although young trauma victims are often resilient, many experience mental health difficulties, including PTSD. Data were collected on two occasions, beginning of December 2005 and end of May 2006, by using a self-evaluation survey method for measuring symptoms of posttraumatic stress disorder (PTSD) according to DSM IV. This study suggests that work with students by giving them psychosocial support within the School Project resulted in significant reduction of PTSD symptoms’ severity.